KERAGAMAN DAN AKTIFITAS LALAT PENGGANGGU DI PETERNAKAN SAPI SEMI EKSTENSIF - Aven Bernard Oematan; Devi Y J A Moenek (Partner, 2018)
Flies are an important vector in directing disease to livestock. It can cause economic losses for farmers such as decreasing the selling price of livestock products, especially meat and milk while losses to livestock are blood loss and weight loss. The aim of this study was to determine thediversity of species, patterns of activity of flies and their relationship to temperature, season, and sex. The research was carried out on semi-intensive cattle farms in the Oli'o dalam kom pasture and Kebun Nitas in Kupang Timur District, Kupang Regency, East Nusa Tenggara. Flies samples were collected using the New Zealand 1 trap. Traps are installed randomly directly at the grazing location, while in cages, traps are placed at a distance of 3-5 meters from the cage guardrail. NZ1 traps are installed from 08:00 until 16:00, then the collection of fly samples is carried out at intervals of two hours from the time of installation, namely 10: 00, 12: 00, 14: 00 and 16: 00. Flies were collected and euthanized with 70% alcohol, then identified by species with identification keys (Dodge 1967) and(Masmeathathip, 2013). Then the data were analyzed descriptively and SEM, from the results of the research obtained by Musca domestika flies, Musca stabulans, Fannia canicularis, haematobia irritans and Tabanus striatus